The Essence of Civil Society in Democracy - Saverinus Rio Jama (Universitas of Muhammadiyah Makassar, 2021)
Abstract. Currently, the role of civil society tends to be stronger in counterbalancing state domination through a democratic system. The state's efforts to create a responsive civil society, namely continuing to instill democratic values based on Pancasila and the 1945 Constitution of the Republic of Indonesia. This article aims to examine the prospects for civil society in a democracy. This research uses a qualitative descriptive approach with the type of literature study with data sources in the form of journals, books, and working papers that are relevant to deductive, inductive, and comparative data analysis. The results show that civil society in the current democracy frame is seen as being able to balance the dominance of the state in policymaking. However, if we look at it, on the other hand, it is quite difficult for us to argue with the actors and political elites, businessmen, and other elites who are not directly involved with the government so that their role is able to determine the wheels of policy as their output even though it may reduce the legitimacy of the state. This is also when we elaborate with the theory of democracy according to Robeth Dahl, where basically modern democracy today is strongly influenced by the capitalization and liberalization of the market economy sector which has a significant double impact on the prospect of a complete democracy.Keywords: Civil Society, democracy.Abstrak. Saat ini peran masyarakat sipil cenderung lebih kuat dalam mengimbangi dominasi negara melalui sistem demokrasi. Upaya negara mewujudkan masyarakat sipil yang responsif yaitu terus menanamkan nilai demokratis berdasarkan pancasila dan UUD NRI Tahun 1945. Artikel ini bertujuan untuk mengulas tentang prospek masyarakat sipil dalam demokrasi. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan jenis studi kepustakaan dengan sumber data berupa jurnal, buku-buku, dan working paper yang relevan dengan analisis data deduktif, induktif, dan komparatif. Hasil penelitian menunjukkan bahwa masyarakat sipil dalam bingkai demokrasi saat ini dipandang mampu mengimbangin dominasi negara dalam penentuan kebijakan. Namun apabila kita cermati dilain sisi bahwa cukup sulit kita bantah terkait para aktor dan elit politik, pengusaha, dan elit yang lainya secara tidak lansung terlibat dengan pemerintah hingga peran mereka mampu menentukan roda kebijakan sebagai outputnya meski kemungkinan mengurangi legitimasi negara. Hal ini juga apabila kita elaborasi dengan teori deokrasi menurut Robeth Dahl dimana pada dasarnya demokrasi modern saat ini memang kuat dipengaruhi oleh kapitalisasi dan liberalisasi sektor ekonomi pasar yang signifikan berdampak ganda pada prospek demokrasi yang utuh.Kata Kunci: Masyarakat Sipil, demokrasi